PENGARUH DEBT TO EQUITY RATIO, RETURN ON INVESTMENT DAN KEBIJAKAN DEVIDEN SEBAGAI VARIABEL MODERATING TERHADAP RETURN SAHAM - Ailia setianingsih; Raden Irna Afriani; Emil Dahlia Wiguna (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2021)
Financial ratios provide information about a company's financial performance and are used as a basis for valuing company stocks that are able to provide high rates of return. The purpose of this study is to determine the effect of debt to equy ratio on stock returns, the effect of return on investment on stock returns, whether dividend policy is able to moderate the relationship between debt to equity ratio on stock returns, and find out whether dividend policy is able to moderate the relationship between return on investment on stock returns This research uses quantitative methods. The research sample was taken from 8 property and real estate subsector companies listed on the Indonesia Stock Exchange in 2015-2019, using 8 purposive sampling techniques. Data collection techniques in this study using secondary data using literature study and documentation. The results of the study are the debt to equity ratio does not significantly influence the stock return with tcount of 0.638 and ttable of 2.026 (0.638 <2.026) with a significance level of 0.528> 0.05. Return on investment does not significantly influence stock returns with a tcount of 1.827 and a table of 2.026 (1.827 <2.026) with a significance level of 0.076> 0.05. Dividend policy is not able to significantly moderate the effect of debt to equity ratio on stock returns. This is indicated by the Rsquare value of the interaction between dividend policy and debt to equity ratio, the results obtained by 0.074 with a significance value of 0.454> 0.05. Dividend policy is not able to significantly moderate the effect of return on investment on stock returns. This is indicated by the Rsquare value of the interaction between dividend policy and return on investment obtained a result of 0.177 with a significance value of 0.355> 0.05. The conclusion in this study is the debt to equity ratio and return on investment does not significantly influence stock returns and dividend policy is not able to significantly moderate the effect of debt to equity ratio and return on investment on stock returns. Keywords: Debt to Equity Ratio, Return On Investment, Dividend Policy, Stock Return